2021
DOI: 10.30589/pgr.v5i3.391
|View full text |Cite
|
Sign up to set email alerts
|

The Possibilities for an Urban Community Action Plan and Collaborative Work Support for Slum Improvement: A Case Study in Jakarta

Abstract: This study describes community development in the preparation for a community action plan for slum management in DKI Jakarta. The case study chosen for this research is the Akuarium village. The existence of slums is an inseparable part of the development of a city. The slum area contributes to several problems such as population density, building conditions, ventilation, sanitation, garbage, drainage, environmental roads, lighting and building layout. In an effort to overcome these problems, it is important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…This result fulfils participation governance that promotes equity and inclusion (Sridhar et al , 2020). Research has shown that stakeholders are experts in constructing slum management action plans that align with participation, collaboration and empowerment (Fadli and Sarofah, 2021). Stakeholders have also provided a platform for the inhabitants to express their views on policies affecting their lives, as well as provide policy feedback to the government.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result fulfils participation governance that promotes equity and inclusion (Sridhar et al , 2020). Research has shown that stakeholders are experts in constructing slum management action plans that align with participation, collaboration and empowerment (Fadli and Sarofah, 2021). Stakeholders have also provided a platform for the inhabitants to express their views on policies affecting their lives, as well as provide policy feedback to the government.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Alaraji (2016) declares that stakeholders’ contributions in the field of education have positively enhanced the self-confidence among some of the underprivileged children in the slums. Relatedly, in policy planning, Fadli and Sarofah (2021) note that stakeholders have helped in crafting slum management action plans using the concepts of participation, sustainable development, empowerment and teamwork. This means stakeholders’ contributions towards slums are multifaceted and span across projects to health and education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the field of career enhancement, Alaraji (2016) highlights the achievement of stakeholders in education that tended to enhance the self-confidence of children in the slums. In the same vein, Fadli and Sarofah (2021) asserted that stakeholders have been exceptional in designing slum governance plans that align with sustainable development. It is of no surprise that Aliu et al (2021) call for stakeholders’ involvement in slum administration to safeguard them from societal deprivation in the areas of basic services denied them.…”
Section: Literature Reviewmentioning
confidence: 99%